Malware attribution - Foo, Ce Zhi (2018)
The report presents the final year project to design and develop an application that performs malware attributions. Malware attributions are critical pieces of Indicators of Compromise (IOC) data to facilitate in the mapping and establishment of the observed cyber-attack. The tool aims to perform a malware attribution of an input file and subsequently, outputs the analysis in a report according to a determined threat intel format. The purpose of the report is for sharing and collaboration within the community.